2019
DOI: 10.1016/j.jesp.2019.103847
|View full text |Cite
|
Sign up to set email alerts
|

Comparing value coding models of context-dependence in social choice

Abstract: Decision-makers consistently exhibit violations of rational choice theory when they choose among several alternatives in a set (e.g., failing to buy the best product in a set when it is presented alongside high-quality alternatives). Many of society's most significant social decisions similarly involve the joint evaluation of multiple candidates. Are social decisions subject to the same violations, and if so, what account best characterizes the nature of the violations? Across five studies, we tested whether d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…Divisive normalization has been proposed as a canonical neural computation that is remarkably ubiquitous in the brain 2 , and there is substantial evidence that neural representations of subject value also exhibit this 3 , 34 or related forms 35 37 of adaptation to the range of offered values. However, the evidence for a behavioral impact of divisive normalization or value-range adaptation appears to be mixed, with some studies reporting positive evidence 4 , 38 but other studies reporting null findings 12 , 34 , 36 , 39 or even contradictory effects 40 . Importantly, the above-mentioned studies are not direct replications of the seminal study by Louie and colleagues 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Divisive normalization has been proposed as a canonical neural computation that is remarkably ubiquitous in the brain 2 , and there is substantial evidence that neural representations of subject value also exhibit this 3 , 34 or related forms 35 37 of adaptation to the range of offered values. However, the evidence for a behavioral impact of divisive normalization or value-range adaptation appears to be mixed, with some studies reporting positive evidence 4 , 38 but other studies reporting null findings 12 , 34 , 36 , 39 or even contradictory effects 40 . Importantly, the above-mentioned studies are not direct replications of the seminal study by Louie and colleagues 4 .…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the better the worst option in a choice set is, the less likely people are to choose the option with the highest value among the remaining options [49]. However, a failed replication of the original study [50] and reversals of this effect in a similar setting [51] cast doubt on whether choices that are based on integrated value representations reliably lead to context effects (but see [52,53] for an on-going debate). Attempts with other ELUSIVENESS OF CONTEXT EFFECTS 9 naturalistic stimuli (e.g., movies) also failed to find robust context effects [29,54].…”
Section: Attribute Concretenessmentioning
confidence: 99%
“…The assumptions of rationality also dictate that preferences between different choice alternatives should be unaffected by availability or quality of other options, an assumption known as intransitivity of preferences (Chang, Gershman, and Cikara 2019). That is, if Option A is preferred over Option B, and Option B is preferred over Option C, then Option A should also always be preferred over Option C. Again, research shows this is not always the case.…”
Section: Lessons From Psychology and Behavioral Economics For The Stu...mentioning
confidence: 99%